Phosphine-catalyzed fixation of CO2 with γ-hydroxyl alkynone under ambient temperature and pressure: kinetic resolution and further conversion. Issue 14 (29th May 2019) - Sun, Yao-Liang; Wei, Yin; Shi, Min
Abstract : Phosphine-catalyzed fixation of CO2 with γ-hydroxyl alkynone under ambient temperature and pressure was achieved and the first example of chiral phosphine catalyzed kinetic resolution of propargyl alcohols via carbon dioxide fixation was demonstrated. Abstract : Multiple skeleton derived γ-hydroxyl alkynones could be activated by phosphine, which then underwent cycloaddition with CO2 to afford functionalized carbonate products under ambient temperature and pressure. These functionalized carbonate products could easily release CO2 under heating conditions, giving a diversity of furanones in excellent yields. The optically active functionalized cyclic carbonates could be afforded through the kinetic resolution of propargyl alcohols via carbon dioxide fixation catalyzed by a new series of sterically hindered and highly nucleophilic bifunctional amino acid-derived phosphine catalysts with moderate to excellent selectivities. Plausible mechanisms were proposed and supported by isotope-labeling experiments and DFT calculations.